Dynamic event-triggered sliding-mode fault-tolerant bipartite consensus control for multi-agent systems based on adaptive observer - Fu , Xingjian; Xia , Dexian (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
For a class of nonlinear second-order leader-follower multi-agent systems with actuator faults, an adaptive observer-based dynamic event-triggered sliding-mode fault-tolerant bipartite consensus control strategy is proposed. Firstly, an adaptive fault observer is designed. The position, velocity and actuator fault degree of the agents at the current moment are obtained. Secondly, a dynamic event-triggered mechanism is proposed to save network resources. Then, a dynamic sliding-mode face and a sliding-mode fault-tolerant bipartite consensus control strategy are given based on the output of the fault observer and the dynamic event-triggered mechanism. So that the bipartite consensus of the second-order multi-agent system can still be realized when there is an actuator fault. The conditions for the convergence of the error of fault-tolerant bipartite consensus for multi-agent systems are given. Finally, in a leader-follower multi-agent system connected by an undirected graph, the effectiveness of the designed control strategy is verified through simulations.